Pengelolaan Zakat dalam Konteks Sistem Ekonomi Islam - Suraya Murcitaningrum; Muhammad Machsun (Journal Of Business, Finance, and Economics (JBFE), 2024)
The Islamic economic model is designed to establish a just and prosperous society by integrating principles of social justice and prosperity into every aspect of life. This approach provides a framework for developing human civilization comprehensively and its implementation is increasingly urgent in the context of zakat management. Zakat, as a fundamental pillar of Islamic economics, plays a crucial role in achieving justice and societal well-being.In this context, an analysis of zakat management systems reveals that traditional approaches often fail to align with the principles of zakat as outlined in the Qur'an and Sunnah. The current distribution methods frequently do not account for individual needs, leading to reduced effectiveness in poverty alleviation and enhancement of welfare. To address these issues, it is essential to evaluate and adjust distribution methods in accordance with zakat principles, and to adopt a more structured and professional management system.Furthermore, enhancing understanding of Islamic economic principles among both the public and zakat administrators is crucial. Implementing principles such as justice and social responsibility should underpin the design and execution of zakat programs. By employing a more organized and transparent approach, along with the use of information technology, zakat management can achieve a more significant and sustainable social impact. Through evaluating and adjusting existing systems and applying deeper Islamic economic principles, it is hoped that zakat management can become more effective in empowering communities and improving welfare equitably.